TRANSFORMASI BOTOL PLASTIK AQUA MENJADI TEMPAT SAMPAH RAMAH LINGKUNGAN BERBASIS KEARIFAN LOKAL DESA BAWOLOWALANGI - Telaumbanu, Tatema; Murnihati Sarumaha; Kaminudin Telaumbanua; Baziduhu Laia; Fatolosa Hulu; Harefa, Darmawan; Anita Zagoto; Dakhi, Agustin Sukses (Haga : Jurnal Pengabdian Kepada Masyarakat, 2025)
Plastic waste management poses a significant challenge in many villages, including Desa Bawolowalangi. The community service program titled “Transformation of Aqua Plastic Bottles into Environmentally Friendly Trash Bins Based on Local Wisdom in Desa Bawolowalangi” aims to address this issue through innovative recycling that integrates local cultural values. This activity involves technical training on recycling aqua plastic bottles as well as the application of motifs and designs unique to Desa Bawolowalangi on trash bin products. This participatory and sustainable approach not only raises environmental awareness but also strengthens cultural identity and opens new economic opportunities for the local community. As a result, the recycled products are not only environmentally friendly but also have high market value, contributing to improved community welfare. Assistance in production management and digital marketing further strengthens the program’s sustainability. These findings demonstrate that integrating local wisdom in waste management can be an effective strategy to empower communities while preserving environmental sustainability. This program is expected to serve as an innovative and sustainable waste management model for other villages in Indonesia.